ECO- FRIENDLY POLYSULFONE TRICOMPOSITE FOR DUAL PROTECTION FROM UV RAYS - Mahmood Raouf, Raouf; Murshed Owaid, Khalid; Mizher Rahma, Nisreen (Journal of Engineering and Sustainable Development, 2018)
A Transparent nanocomposite consist of polysulfone (PSF), cellulose acetate butyrate (CAB) and nano indium oxide (nanoIn2O3) was prepared by melting and re-molding so as to safeguard from the impact of ultraviolet rays. By means of scanning electron microscope (SEM), X-ray diffraction (XRD), UV-Vis spectroscopy, dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA), the morphological, optical, mechanical and thermal properties were studied. As we reported before that PSF/0.2%CAB implies low ultraviolet light absorption for PSF and CAB transparent blend. In the present study, we investigated the effect of nanoIn2O3 on the characteristics of PSF/0.2%CAB/nanoIn2O3 Tricomposite. The results showed that the inorganic nano particles are well dispersed in the PSF matrix without macro phase separation, as well as assisting to spread the organic component CAB. The UV-Vis spectroscopy showed that 0.02%nanoIn2O3 is able to shield PSF from UV radiation. So, we've got dual protection transparent eco-friendly nanocomposite from UV rays and is also able to protect the surfaces from the impact of these rays if used as a protection them. The XRD pattern of pure PSF clarified that there is a noticeable decrease in the bundle peaks in bi-composite and Tricomposite pattern. Furthermore, the Tricomposite showed high stability to temperatures lower than Tɡ.